The Use of Iliac Side Branch Devices in Patients with Aortoiliac Aneurysm - Maus, V.; Kurz, P.; Sommer, C. M.; Massmann, A.; Hatopp, A.; Erpenbach, S.; Thomas, K.; Saalmüller, T.; Meißner, H.; Hupp, T.; Richter, G. M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: The aim of this study was to evaluate the technical feasibility and short-time patency rate of iliac side branch devices based on the authors’ institution’s experience.Materials and Methods: Data of 17 patients (all men) with an aortoiliac aneurysm (median age 72.5 years) who underwent endovascular repair between October 2013 and June 2015 (20 months) at our institution was analyzed retrospectively. Primary endpoint was primary technical success, defined as adequate implantation of the iliac branch device with patency of the hypogastric side branch without the need of further re-interventions within 30 days. Mean follow-up was 8.2 ± 5.4 months.Results: Eighteen iliac side branch devices were implanted with a branch patency of 100 % and a primary technical success rate of 94.4 % (n = 17). Perioperative 30 days mortality was 0 %. The mean diameter of treated abdominal aorta and common iliac artery was 41 ± 14 and 30 ± 8 mm. In one case partial dislocation of the iliac side branch device occurred due to severe kinking of iliac arteries with development of an iliac endoleak type Ib that had to be treated in a second intervention. Three patients (15 %) showed an endoleak type II from the inferior mesenteric artery without the need of re-intervention. After three months one patient suffered from subtotal thrombotic occlusion of the bridging stent that was successfully resolved through intra-arterial fibrinolytic therapy and additional stent graft implantation.Conclusion: Summarized, implantation of iliac side branch devices is a feasible technique with favourable short-term results in patients with aortoiliac aneurysm.Key Points:• Implantation of iliac side branch devices is a feasible technique.• Distinguish short-term results of side branch endografting in patients with aortoiliac aneurysm.• Carefully patient selection is necessary to avoid complications and re-interventions.Citation Format:• Maus V, Kurz P, Sommer CM et al. The Use of Iliac Side Branch Devices in Patients with Aortoiliac Aneurysm.. Fortschr Röntgenstr 2016; 188: 746 – 752
Keywords: endovascular aortic repair; aortic aneurysm; iliac artery aneurysm; iliac side branch device; endoleak